2013
DOI: 10.1103/physrevb.88.144404
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic ordering and half-metallic state of Sn2Co3S2with the shandite-type structure

Abstract: Single crystalline Sn 2 Co 3 S 2 with the shandite-type structure was investigated by magnetization, magnetoresistance, Hall effect, and heat capacity measurements and by 119 Sn Mößbauer spectroscopy. Sn 2 Co 3 S 2 orders ferromagnetically at 172 K with an easy-axis magnetization of ≈1 μ B along the hexagonal c axis. The half-metallic ferromagnetic state is investigated by detailed band-structure calculations by density functional theory (DFT) methods. The magnetoresistance and the Hall effect as well as the D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
111
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 32 publications
(60 reference statements)
19
111
0
Order By: Relevance
“…The Curie temperature, T C , and spontaneous moment, m s , in the easy c-axis at 2 K of Co 3 Sn 2 S 2 are found to be 174 K and 0.26 m B /Co, respectively, as estimated by the Arrott plot of magnetic isotherms (not shown). The obtained T C and m s coincide well the recently reported results using single crystals [15,20]. With increasing of the In concentration, the ferromagnetic order is suppressed and collapsed around x c $ 0.8.…”
Section: Structure and Lattice Parameterssupporting
confidence: 90%
See 3 more Smart Citations
“…The Curie temperature, T C , and spontaneous moment, m s , in the easy c-axis at 2 K of Co 3 Sn 2 S 2 are found to be 174 K and 0.26 m B /Co, respectively, as estimated by the Arrott plot of magnetic isotherms (not shown). The obtained T C and m s coincide well the recently reported results using single crystals [15,20]. With increasing of the In concentration, the ferromagnetic order is suppressed and collapsed around x c $ 0.8.…”
Section: Structure and Lattice Parameterssupporting
confidence: 90%
“…Theoretical band-structure calculations and photoemission study indicated a half metalicity of the ferromagnetic state of Co 3 Sn 2 S 2 [9,15,17] which is classified as a type I A half-metallic ferromagnet [18]. The counterpart Co 3 In 2 S 2 was predicted as a paramagnetic metal by recent theoretical band calculations [19], which implies the ferromagnetic quantum phase transition by the In-substitution for Sn in Co 3 Sn 2 À x In x S 2 series.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…1. Previous studies of the magnetization process of the half metallic ferromagnet Co 3 Sn 2 S 2 26,27 have explored high axial anisotropy in temperature and field dependences of the magnetization 28,29 . The Curie temperature, T C , and the spontaneous moment, M s , at 2 K in the easy c-axis were reported as 174 K and ~0.3 µ B /Co, respectively.…”
Section: Introductionmentioning
confidence: 99%